Риски реализации принципа гуманизма в правоприменении - Тімофєєва, Лілія Юріївна; Тимофеева, Лилия Юрьевна; Timofeeva, Lily Yu. (My University, 2014)
Эта статья о рисках реализации принципа гуманизма в правоприменении. Было исследовано сбалансированную реализацию принципа гуманизма в отношении субъектов уголовно-правовых отношений. К ним относятся: преступник, потерпевший, общество и государство. Некоторые ученые называют гуманизм «опасной философией». Исследованы опасности, риски, связанные с нарушением баланса, с чрезмерной или недостаточной реализацией принципа гуманизма.

Ця стаття про ризики реалізації принципу гуманізму в правозастосуванні. Було досліджено збалансовану реалізацію принципу гуманізму щодо суб'єктів кримінально-правових відносин. До них відносяться: злочинець, потерпілий, суспільство і держава. Деякі вчені називають гуманізм «небезпечною філософією». Досліджено ризики, пов'язані з порушенням балансу, з надмірною або недостатньою реалізацією принципу гуманізму.

As democratic societies subject to the rule of law their national authorities need to balance community interests against the basic human rights of individuals. Scientist researched realization the principle of humanism. There are N. A. Lopashenko, N. A. Orlova, T. R. Sabitov, V. A. Tulyakov, V. D. Filimonov, N.I. Havronyuk etc. This article is about the risks realization the principle of humanism in law enforcement. The research based on positions of international law, national, foreign legislation and crime law doctrine. Criminal law shall ensure the safety of man. It is a main idea. The principles of humanism reflects of the institute of softening, aggravating circumstances, retroactive effect of the law on criminal liability in time, discharge on probation, juvenile justice, amnesty, pardon etc. We researched principle of humanism as general principle of law with criminal law specific. We researched balanced realization the principle of humanism as to subjects of criminal law relations. There are criminal, victim, society and the state. Paradoxically, some of the scientist and critics of principle of humanism maintain that it is a dangerous philosophy. Dangerous, risks associated with an imbalance, with excessive or insufficient balanced realization the principle of humanism. Punishment is a pain. Crime does not exist as a natural phenomenon. The criminal law should prohibit something only if absolutely necessary. We cannot abolish the penal institution totally. We cannot abolish the humanism totally. We need researched balanced realization the principle of humanism.
Тимофеева Л. Ю. Риски реализации принципа гуманизма в правоприменении / Л. Ю. Тимофеева // Електронне наукове видання «Юридичний науковий електронний журнал». – 2014. – № 5. – С. 1. [Електронний ресурс]. – Режим доступу: www.lsej.org.ua/ indexs.php/nomery-zhurnalu?id=33.
Keywords: аболиционизм; баланс; принцип; потерпевший; правоприменение; риски; аболіціонізм; баланс; гуманізм; потерпілий; правозастосування; ризики; abolitionism; balance; humanism; the principle; the victim; law enforcement; risks